1991
DOI: 10.1007/bf00312764
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a Candida tsukubaensis ?-glucosidase gene in the yeast Saccharomyces cerevisiae

Abstract: The molecular cloning of an alpha-glucosidase gene isolated from a Candida tsukubaensis (CBS 6389) genomic library in Saccharomyces cervisiae is reported. The cloned gene is contained within a 6.2 kb Sau3A DNA fragment and directs the synthesis and secretion of an amylolytic enzyme into the extracellular medium of the recombinant host, S. cerevisiae. The cloned enzyme was found to have an unusually broad substrate specificity and is capable of hydrolysing alpha-1,2, alpha-1,3, alpha-1,4 and alpha-1,6 linked, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…pombe (Okuyama et al , 2001) or S. fibuligera (Hostinova et al , 2005) enzymes is about 105 kDa. A heterodimeric α‐glucosidase has been studied in C. tsukubaensis (52 and 65 kDa) (Kinsella et al , 1991). Usually, fungal α‐glucosidases consist of two subunits synthesized from one precursor peptide chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pombe (Okuyama et al , 2001) or S. fibuligera (Hostinova et al , 2005) enzymes is about 105 kDa. A heterodimeric α‐glucosidase has been studied in C. tsukubaensis (52 and 65 kDa) (Kinsella et al , 1991). Usually, fungal α‐glucosidases consist of two subunits synthesized from one precursor peptide chain.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast α‐glucosidases are found in 13 and 31 families and generally are from types II or I. Different biochemical and/or molecular aspects of the enzymes from yeast such as Candida tsukubaensis (Kinsella et al , 1991), Candida albicans (Geber et al , 1992), Torulaspora pretoriensis (Oda et al , 1993), Schizosaccharomyces pombe (Okuyama et al , 2001), Hansenula polymorpha (Liiv et al , 2001), Saccharomyces cerevisiae (Yamamoto et al , 2004) or Saccharomycopsis fibuligera (Hostinova et al , 2005) have been reported. In addition, the number of genomes sequenced has been increasing considerably in the last decade and analysis of the information generated shows a considerable number of putative α‐glucosidases.…”
Section: Introductionmentioning
confidence: 99%
“…Northern analysis revealed that maltase mRNA was induced twice as much in maltoseversus sucrose-grown cells (Fig. 4) (25), Schwanniomyces castellii (8,9), Candida tsukubaensis (18,19), and Candida tropicalis (32). Little information regarding the substrate specificity and regulation of the C. albicans glucoamylase is available (5,26), and a role for this enzyme in sucrose utilization cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Little information regarding the substrate specificity and regulation of the C. albicans glucoamylase is available (5,26), and a role for this enzyme in sucrose utilization cannot be excluded. However, we did not isolate this gene from our cDNA library by using an assay capable of detecting the glucoamylase activity of C. tsukubaensis (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…10,11) The promoter sequences of native GPDencoding genes have proven useful for efficient expression of heterologous genes in several yeasts and fungi. 10,[12][13][14][15] In the case of -glucosidase from P. tsukubaensis, the gene with its native promoter region has been efficiently expressed in Saccharomyces cerevisiae, 16) demonstrating the expression ability of theglucosidase promoter in different species.…”
mentioning
confidence: 99%